Microaggregates in soils. Issue 1 (11th August 2017) - Totsche, Kai Uwe; Amelung, Wulf; Gerzabek, Martin H.; Guggenberger, Georg; Klumpp, Erwin; Knief, Claudia; Lehndorff, Eva; Mikutta, Robert; Peth, Stephan; Prechtel, Alexander; Ray, Nadja; Kögel-Knabner, Ingrid
Abstract: All soils harbor microaggregates, i.e ., compound soil structures smaller than 250 µm. These microaggregates are composed of diverse mineral, organic and biotic materials that are bound together during pedogenesis by various physical, chemical and biological processes. Consequently, microaggregates can withstand strong mechanical and physicochemical stresses and survive slaking in water, allowing them to persist in soils for several decades. Together with the physiochemical heterogeneity of their surfaces, the three‐dimensional structure of microaggregates provides a large variety of ecological niches that contribute to the vast biological diversity found in soils. As reported for larger aggregate units, microaggregates are composed of smaller building units that become more complex with increasing size. In this context, organo‐mineral associations can be considered structural units of soil aggregates and as nanoparticulate fractions of the microaggregates themselves. The mineral phases considered to be the most important as microaggregate forming materials are the clay minerals and Fe‐ and Al‐(hydr)oxides. Within microaggregates, minerals are bound together primarily by physicochemical and chemical interactions involving cementing and gluing agents. The former comprise, among others, carbonates and the short‐range ordered phases of Fe, Mn, and Al. The latter comprise organic materials of diverse origin and probably involve macromolecules and macromolecular mixtures. Work on microaggregate structure and development has largely focused on organic matter stability and turnover. However, little is known concerning the role microaggregates play in the fate of elements like Si, Fe, Al, P, and S. More recently, the role of microaggregates in the formation of microhabitats and the biogeography and diversity of microbial communities has been investigated. Little is known regarding how microaggregates and their properties change in time, which strongly limits our understanding of micro‐scale soil structure dynamics. Similarly, only limited information is available on the mechanical stability of microaggregates, while essentially nothing is known about the flow and transport of fluids and solutes within the micro‐ and nanoporous microaggregate systems. Any quantitative approaches being developed for the modeling of formation, structure and properties of microaggregates are, therefore, in their infancy. We respond to the growing awareness of the importance of microaggregates for the structure, properties and functions of soils by reviewing what is currently known about the formation, composition and turnover of microaggregates. We aim to provide a better understanding of their role in soil function, and to present the major unknowns in current microaggregate research. We propose a harmonized concept for aggregates in soils that explicitly considers the structure and build‐up of microaggregates and the role of organo‐mineral associations. We call for experiments, studies and modeling endeavors that will link information on aggregate forming materials with their functional properties across a range of scales in order to better understand microaggregate formation and turnover. Finally, we hope to inspire a novel cohort of soil scientists that they might focus their research on improving our understanding of the role of microaggregates within the system of aggregates and so help to develop a unified and quantitative concept of aggregation processes in soils.